Increased serum cartilage oligomeric matrix protein levels and decreased patellar bone mineral density in patients with chondromalacia patellae. Issue 11 (1st November 2002) - Murphy, E; FitzGerald, O; Saxne, T; Bresnihan, B
Abstract : Background: Chondromalacia patellae is a potentially disabling disorder characterised by features of patellar cartilage degradation. Objective: To evaluate markers of cartilage and bone turnover in patients with chondromalacia patellae. Methods: 18 patients with chondromalacia patellae were studied. Serum cartilage oligomeric matrix protein (s-COMP) and bone sialoprotein (s-BSP) levels were measured by enzyme linked immunosorbent assay (ELISA) and compared with those of age and sex matched healthy control subjects. Periarticular bone mineral density (BMD) of both knee joints was assessed by dual energy x ray absorptiometry (DXA). Results: s-COMP levels were significantly raised in all patients with chondromalacia patellae compared with healthy control subjects (p=0.0001). s-BSP levels did not differ significantly between the groups (p=0.41). BMD of the patella was significantly reduced in patients with chondromalacia patellae compared with the control subjects (p=0.016). In patients with bilateral chondromalacia patellae, BMD of the patella was lower in the more symptomatic knee joint (p=0.005). Changes in periarticular BMD were localised to the patella and were not present in femoral regions. Neither s-COMP (p=0.18) nor s-BSP (p=0.40) levels correlated with patellar BMD. Conclusions: Increased s-COMP levels, reflecting cartilage degradation, and reduced BMD localised to the patella may represent clinically useful markers in the diagnosis and monitoring of patients with chondromalacia patellae. Measures of cartilage degradation did not correlate with loss of patellar bone density, suggesting dissociated pathophysiological mechanisms.